Which Online Quiz Platform Works Best for Arabic at Senior High School?: A Comparative Empirical Study of Blooket, Quizizz, Wordwall, and Kahoot - Doni, Chaterina Puteri; Hasibuan, Renni; Muhammad Jundi; Saleh, Sriwahyuningsih R; Pakaya, Nurul Aini; Sarif, Suharia (Institut Agama Islam Negeri (IAIN) Kendari, 2025)
Gamification has emerged as a transformative approach in language education, especially for digitally native senior high school students who thrive in interactive and engaging environments. This study presents a comparative empirical analysis of four gamified online interactive quiz platform (Blooket, Quizizz, Kahoot, and Wordwall) in their effectiveness for Arabic language learning at senior high school. Leveraging a quasi-experimental pretest-posttest design, thirty-eight students were divided into experimental and control groups based on existing classes. After a five-session intervention, a 30-item posttest was administered, and the results were statistically analyzed using paired sample t-test and one-way ANOVA. The results showed no significant differences in post-test scores across the four platforms, indicating comparable effectiveness in supporting student learning outcomes. However, t-test results revealed a greater score improvement with Blooket, a finding consistent with students’ strong preference for this platform. The higher engagement offered by Blooket’s varied and complex gamification features suggests that platform design may substantially influence learner motivation and performance, in line with existing literature on gamified learning environments. This study enriches the discourse on game-based learning (GBL), emphasizing the value of digital tools in fostering effective and enjoyable classroom experiences.